Philippine Indigenous Forts in Accounts from the 16th to 20th Centuries - Wright, Ma. Elena (Hukay, 2022)
The paper is an initial attempt at a descriptive summary of the different kinds of indigenous fortifications found in several Philippine provinces. The data for this paper were gathered from library and internet resources containing historical accounts of foreign observers as well as the folklore of some indigenous people. Philippine archaeology, being still in its youth, has only studied the ijangs of Batanes province as natural fortifications. But in different historical accounts and local folklore, there are mentions of fortifications that local inhabitants used as a means of refuge and defence against their enemies long before Spanish colonizers came to the Philippines in the early 16th century. These indigenous fortifications may be classified under two basic groups—natural and man-made. Inaccessible landforms and very tall trees are the usual examples of natural forts. Man-made forts are constructed using materials abundantly found in the environment such as wood, bamboo, rocks, and earth. Much is yet to be studied about Philippine indigenous forts. This paper is an initial attempt at identifying different kinds of indigenous fortifications which can help determine prospective sites that may be studied in the future. Keywords: fortification, southeast Asian forts, historical warfare